KARAKTERISTIK MORFOLOGI KANGURU POHON CENDERAWASIH (Dendrolagus ursinus) DI KAWASAN PEGUNUNGAN ARFAK MANOKWARI - Jannie T. Mustamu; F. Dwiranti; Aksamina M. Yohanita (FMIPA Universitas Papua, 2008)
This research was carried out to study the morphological charachteristics of the tree kanguroo in the Arfak Mountains, especially in the village of Mokwam and Umbui. Observation was done on the qualitative and quantitative charachters. Four kanguroo tree was observed during the study.